2012 International Conference on ICT Convergence (ICTC) 2012
DOI: 10.1109/ictc.2012.6387195
|View full text |Cite
|
Sign up to set email alerts
|

Robust LTE uplink scheduling based on call admission control

Abstract: In LTE system, it is difficult for an eNB to properly allocate uplink resource blocks (RBs) to UEs as many factors complicate the issue. So far, most research has focused on maximizing system throughput. However, this is often achieved by downgrading other performance metrics and may result in the waste of resources. In this paper, a resource allocation scheme for LTE uplink is proposed which takes into account the data rate granted by call admission control (CAC). Data rate is defined based on exponentially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…AAG scheme follows the constraint in which RBs allocated to a UE must be contiguous and must use the lowest available modulation-coding scheme (MCS). Simulation results have shown that AAG provides shorter packet delays and higher system throughput and UE satisfaction than those achieved using the RME and RR schemes under the scenarios simulated in [16].…”
Section: Previous Work -Aag Scheduling Schemementioning
confidence: 89%
See 3 more Smart Citations
“…AAG scheme follows the constraint in which RBs allocated to a UE must be contiguous and must use the lowest available modulation-coding scheme (MCS). Simulation results have shown that AAG provides shorter packet delays and higher system throughput and UE satisfaction than those achieved using the RME and RR schemes under the scenarios simulated in [16].…”
Section: Previous Work -Aag Scheduling Schemementioning
confidence: 89%
“…We have demonstrated the excellent performance of AAG in [16] and the functionality of AAG-2 in Section 5. In the following, we demonstrate the functionality of AAG-D in an Table 3 environment that differs somewhat from that used in Section 5.…”
Section: Performance Evaluation For Aag-dmentioning
confidence: 92%
See 2 more Smart Citations
“…In section IV we will present a novel scheme AAG-2 that not only ensures QoS for GBR bearers but also offers a certain level of service for non-GBR bearers at the same time. AAG-2 builds on AAG which was presented in [14,15]. For sake of completeness, we briefly describe the operation of AAG in the follows.…”
Section: Previous Work -Aag Scheduling Schemementioning
confidence: 99%